4CPS-003 Outpatient-reported experience in hospital pharmacy ambulatory care during the COVID-19 pandemic. (23rd March 2022) - Lobo Alves, M; Paróla, A; Atalaia, A; Viegas, E; Mirco, A; Farinha, H; Falcão, F
Abstract : Background and importance: Measuring health care quality and performance is a major challenge in improving health systems' efficiency. Patient experience is an important health care quality measure; thus, use of questionnaires reporting patients' experience and perceptions while receiving care is recommended. The COVID-19 pandemic has accelerated the establishment of proximity dispensation models and ambulatory care redesign, aligned with the Anaesthesia Clinical Services Accreditation (ACSA) accreditation model, implemented in 2019 in the Pharmacy Department. Aim and objectives: Evaluate patient-reported experience regarding outpatient care in a central hospital pharmacy, during the COVID-19 pandemic. Material and methods: Single-centre cross-sectional study (March–June 2021). Ambulatory outpatients were invited to complete a survey, consisting of 14 questions on: access to care, waiting time, communication and information about medication, pharmaceutical care provider (pharmacist in charge), privacy/confidentiality and unmet needs. The survey was made available to patients in paper or digital format at the pharmacist consultation, teleconsultation, medicines home delivery and pharmadrive delivery. Results: A total of 9634 outpatients attended our ambulatory care during the study period. We carried out 1939 teleconsultations, 2194 home deliveries and 91 in-person consultations. Outpatients answered 148 surveys (1.5%). Most patients were pleased to continue picking up medication at hospital pharmacy (86%) and rated the service as good/very good. Patients considered that there was availability to listen/sympathy (99%) and privacy (96%) during the service. Information provided about medication was considered useful (89%). Waiting time was rated as appropriate (90%). A large percentage of patients were unaware of the possibility of pharmadrive (76%) and proximity dispensation (45%). Outpatients knew their pharmacist in charge in 37% of the cases and 75% had already contacted their pharmacist, 32% were not aware of the existence of a pharmacist in charge and the remaining (30%) did not have a pharmacist in charge. Conclusion and relevance: Pharmacists' effort in pandemic times, implementing strategies to improve patient-centredness of care, ensured outpatients' continuity of pharmaceutical care and medicines. In order to engage patients and improve their experience, awareness and retention of pharmacists in charge needs to increase. As improvement measures we intend to improve our outpatient care guide with more detailed information, and will also refresh pharmacist training. References and/or acknowledgements: Conflict of interest: No conflict of interest